Discontinuation of modern hormonal contraceptives: an Italian survey. (1st November 2016) - Fruzzetti, Franca; Perini, Daria; Fornaciari, Lara; Russo, Marinella; Bucci, Fiorella; Gadducci, Angiolo
Abstract: Objectives: The aim of the study was to examine, in a sample of Italian women, the rate of discontinuation of use of hormonal contraception. Methods: In a retrospective cross-sectional study, data were collected from a chart review of 1809 women using or stopping the hormonal contraceptive prescribed by their physician. The name of the contraceptive and the reason for discontinuation were taken from the charts. The differences between the methods regarding reasons for discontinuation were analysed. Results: Of the 1809 women examined, 34.9% had discontinued their hormonal contraception: 6.9% did so for non-method-related reasons, 20.5% due to minor side effects, 4.4% due to major side effects and 3.8% due to difficulties with compliance. Irregular bleeding, weight gain and headache were the main reasons reported for discontinuation. Pills containing 30 μg or 20 μg ethinylestradiol (EE) and the vaginal ring were the most used contraceptive methods. Women using the vaginal ring discontinued less frequently compared with pill users ( p  < .005). Pills containing 20 μg and 30 μg EE had the same discontinuation rate. Venous thrombosis was the most frequently reported major side effect leading to discontinuation. Conclusion: About one-third of women who used modern hormonal contraceptives discontinued the method. Although the percentage of women who gave up as a result of minor side effects was lower than it used to be, and the use of low doses of EE by the vaginal route has decreased the rate of discontinuation, physicians should counsel women about the possibility of side effects and encourage them to seek advice before stopping.